Analysis of the effectiveness of the application of pelvic floor rehabilitation exercise and the factors influencing its self-efficacy in postoperative patients with cervical cancer - Li, Xichun; Liu, Ling; He, Jinhui; Yan, Jue; Wang, Ying (Frontiers in Oncology, 2023)
Objective. To analyze the application effect of pelvic floor rehabilitation exercise in postoperative patients with cervical cancer and the factors influencing their self-efficacy. Methods. The medical records of 120 postoperative patients with cervical cancer from January 2019 to January 2022 were retrospectively collected from the Department of Rehabilitation, Aeronautical Industry Flying Hospital, Bayi Orthopaedic Hospital and Southwest Medical University Affiliated Hospital of Traditional Chinese Medicine, and the Department of Obstetrics and Gynecology, Chengdu Seventh People's Hospital, and the Department of Oncology, Sichuan Provincial People's Hospital. They were divided into routine group (n=44, applied routine care) and exercise group (n=76, applied routine care + pelvic floor rehabilitation exercise) according to the different perioperative care programs. The general data, PFDI-20 scores and broome pelvic muscle self-efficacy scale (BPMSES) scores of patients in the exercise group were investigated and analyzed individually to investigate the factors influencing the self-efficacy of patients with pelvic floor rehabilitation exercise after cervical cancer surgery. Results. The time of first anal exhaust, urine tube retention and hospitalization after surgery were shorter in the exercise group than in the routine group (P<0.05). The bladder function grade I rate after surgery was more in the exercise group than in the routine group, and the urinary retention incidence was lower than that in the routine group (P<0.05). At 2 weeks after exercise, bladder compliance and bladder detrusor systolic pressure were higher in both groups than before exercise, and they were higher in the exercise group than in the routine group (P<0.05). There was no significant difference in urethral closure pressure within and between the two groups (P>0.05). Conclusion. Implementing pelvic floor rehabilitation exercise for postoperative patients with cervical cancer can speed up the recovery of pelvic organ function and reduce the occurrence of postoperative urinary retention. Marital status, residence and PFDI-20 scores were influential factors in the self-efficacy level of patients undergoing pelvic floor rehabilitation exercise after cervical cancer surger, medical staff need to incorporate these clinical features to provide targeted nursing interventions to enhance patient compliance with training and improve postoperative survival quality.